Gamer nation : video games and American culture - Wills, John, 1971- (Johns Hopkins University Press, 2019)
"This book takes a cultural studies approach to analyzing video games for young players. It considers not only how games reflect myths in American culture but also how they propagate those myths through their design, imagery, and scenarios of violence"--